Development and initial psychometric evaluation of the hospitalization-related stressors questionnaire for elderly patients - Zahra Musavi; Mousa Alavi; Nasrollah Alimohammadi; Habibollah Hosseini (Wolters Kluwer Medknow Publications, 2016)
Background: Various factors threaten the health and recovery of hospitalized elderly, including stressors in medical service centers. Therefore, the aim of the present study was to develop and preliminary validate a measurement tool to assess hospitalization-related stressors (HRS) among the elderly. Materials and Methods: This methodological research was conducted in 2015. The study was performed in two main phases. In the first phase, which was to develop the questionnaire, the data were collected through literature review, interview with few elderly patients, and calculating content validity index with the participation of 16 experts. The second phase included preliminary validation of the questionnaire in which a convenient sample of 200 hospitalized elderly patients recruited from 4 educational medical centers of the Isfahan University of Medical Sciences were studied. Principal component analysis method was used to identify the factorial structure of the questionnaire. In order to evaluate validity, Cronbach's alpha coefficient was calculated. Results: After evaluating the results and relocating and merging some of the items, a version of 26 items in 7 categories was prepared with acceptable internal consistency (Cronbach's alpha coefficient from 0.67 to 0.78 for the components and 0.83 for the tool). Conclusions: In this study, we were able to identify a set of important components and indicators of HRS in elderly; so it can be used as a useful instrument. Future studies are recommended in order to develop and validate this tool in other communities.